Recent Progress in Optical Control of Ferroelectric Polarization. Issue 23 (3rd March 2021) - Guo, Jiaxing; Chen, Wenwen; Chen, Haisheng; Zhao, Yanan; Dong, Feng; Liu, Weiwei; Zhang, Yang
Abstract: Manipulation of ferroelectric polarization and associated domain is at the heart of ferroelectric‐based applications. Polarization switching is typically achieved by a static or pulsed electric field, which however suffers from limitations associated with the requirement of circuitry access and the sluggish switching time. To circumvent abovementioned challenges, significant effort has been devoted to optical control of ferroelectric polarization, which can provide tremendous potential to develop ferroelectric devices with more freedom and to extend transient operation down to picosecond time scale. In this review, both the phenomena and the mechanism of optical control over polarization and associated domain evolution are explored in various kinds of ferroelectrics, including oxide perovskites, van der Waals ferroelectrics, and ferroelectric heterostructures, etc. All‐optical fabrication of 3D nonlinear photonic crystals based on femtosecond laser‐induced ferroelectric domain inversion is presented. In particular, some intriguing examples of terahertz field‐induced polarization reversal and paraelectric‐to‐ferroelectric phase transition are highlighted. The review concludes with a brief summary of the related branches, and discusses the challenges as well as the potential directions of this emerging field. Abstract : Optical control of ferroelectric polarization can provide tremendous potential to develop ferroelectric‐based devices with more freedom and to extend transient operation down to picosecond time scale. Recent progress in optical control of ferroelectric polarization with different aspects is reviewed; the challenges as well as the potential directions of this emerging field are discussed.